The Dynamics of Sovereign Debt Crises and Bailouts - Roch, Francisco; Uhlig, Harald (Washington, D.C. : International Monetary Fund, 2016)
Motivated by the recent European debt crisis, this paper investigates the scope for a bailout guarantee in a sovereign debt crisis. Defaults may arise from negative income shocks, government impatience or a "sunspot"-coordinated buyers strike. We introduce a bailout agency, and characterize the minimal actuarially fair intervention that guarantees the no-buyers-strike fundamental equilibrium, relying on the market for residual financing. The intervention makes it cheaper for governments to borrow, inducing them borrow more, leaving default probabilities possibly rather unchanged. The maximal backstop will be pulled precisely when fundamentals worsen.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet